2004
DOI: 10.2105/ajph.94.10.1671
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Institute of Medicine’s Recommended Curriculum Content in Schools of Public Health: A Baseline Assessment

Abstract: In September 2003, the Association of Schools of Public Health administered an online survey to representatives of all 33 accredited US schools of public health. The survey assessed the extent to which the schools were offering curriculum content in the 8 areas recommended by the Institute of Medicine: communication, community-based participatory research, cultural competence, ethics, genomics, global health, informatics, and law/policy. Findings indicated that, for the most part, schools of public health are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…This is in agreement with scholars (Ajzen 1991;Hansen, Jensen, and Solgaard 2004;Shortell et al 2004;Page, Ebersohn, and Rogan 2006;Guo et al 2007), who have suggested that knowledge alone does not influence behaviour. This also echoes view that science literacy alone will not affect morality, character and citizenship.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with scholars (Ajzen 1991;Hansen, Jensen, and Solgaard 2004;Shortell et al 2004;Page, Ebersohn, and Rogan 2006;Guo et al 2007), who have suggested that knowledge alone does not influence behaviour. This also echoes view that science literacy alone will not affect morality, character and citizenship.…”
Section: Discussionsupporting
confidence: 92%
“…Since the release of the Institute of Medicine's reports calling attention to weaknesses in public health training and infrastructure, schools of public health have sought ways to meet the challenges identified. 13,30 Schools have examined their structures and cultures, changed core and academic curricula, and increased collaborative research with state and local HDs. 6,16,22,[31][32][33] Numerous examples of successful collaborations have been developed by schools of public health and HDs, covering a wide range of public health practice areas.…”
Section: Resultsmentioning
confidence: 99%
“…Only 58% of the accredited schools of public health report having a course in cultural competency as part of their curriculum, with even fewer requiring it as part of their core curriculum (48%). 48 Increasing the availability of relevant cultural competency training in public health and other health professions is an important first step toward increasing the relevance and effectiveness of community-level healthpromotion strategies. However, to eliminate disparities, health professionals must also use the principles to engage communities as partners in these efforts.…”
Section: Implications For Health Professionalsmentioning
confidence: 99%